Cultural heritage and development : a framework for action in the Middle East and North Africa - World Bank. (Washington, D.C. : World Bank, 2001)
This strategy research and framework for action study explores the key challenges confronted by Middle East and North Africa countries in integrating patrimony management within their mainstream development policies and programs, in deriving higher benefits from the economic and educational potential of the cultural heritage, in safeguarding the patrimony against accelerated deterioration and loss.
Machine generated contents note: 1. The Cultural Sector in MENA Countries -- A. The Sector: Actors, Assets, Industries, and Instituions -- B. Loss of Patrimony Treasures: Causes and Needs -- II. Cultural Heritage and World Bank Policies -- Ill. Economic Benefits and Poverty Reduction -- through CH Preservation -- IV. World Bank Support for Cultural Heritage -- in the MENA Region -- V. MENA Strategic Priorities and Framework for -- Assistance -- A Strategic Priorities -- B. Operational Steps -- C. Project Preparation Instruments -- D. Strengthening In-House Capacity -- Notes -- References -- Maps -- Illustration Credits.
Includes bibliographical references (p. [91]-95).
Includes illustration credits (p. [101]-102).
rua 06/03/15
Loans
Keywords: Cultural property -- Protection -- Middle East; Cultural property -- Protection -- Africa, North; Economic development -- Social aspects -- Middle East; Economic development -- Social aspects -- Africa, North; World Bank